Advancing equity in accountability and organizational cultures of data use. Issue 4 (3rd July 2017) - Gannon-Slater, Nora; La Londe, Priya G.; Crenshaw, Hope L.; Evans, Margaret E.; Greene, Jennifer C.; Schwandt, Thomas A.
Abstract : Purpose: Data use cultures in schools determine data use practices. Such cultures can be muted by powerful macro accountability and organizational learning cultures. Further, strong equity-oriented data use cultures are challenging to establish. The purpose of this paper is to engage these cultural tensions. Design/methodology/approach: The data discourse and decisions of four grade-level teams in two elementary schools in one district were studied through observation of 62 grade-level meetings over the course of a year. The observations focused on "data talk, " defined as the structure and content of team conversations about interim student performance data. Findings: Distinct macro cultures of accountability and organizational learning existed in the two schools. The teams' own data use cultures partly explained the absence of a focus on equity, and none of the teams used student performance data to make instructional decisions in support of the district's equity aims. Leadership missed opportunities to cultivate an equity-focused data use culture. Practical implications: School leaders who advocate that equity importantly guides data use routines, and can anticipate how cultures of accountability or organizational learning "show up" in data use conversations, will be better prepared to redirect teachers' interpretations of data and clarify expectations of equity reform initiatives. Originality/value: This study is novel in its concept of "data talk, " which provided a holistic but nuanced account of data use practices in grade-level meetings.